2020
DOI: 10.1096/fj.201902855rr
|View full text |Cite
|
Sign up to set email alerts
|

miR‐206 family is important for mitochondrial and muscle function, but not essential for myogenesis in vitro

Abstract: miR‐206, miR‐1a‐1, and miR‐1a‐2 are induced during differentiation of skeletal myoblasts and promote myogenesis in vitro. miR‐206 is required for skeletal muscle regeneration in vivo. Although this miRNA family is hypothesized to play an essential role in differentiation, a triple knock‐out (tKO) of the three genes has not been done to test this hypothesis. We report that tKO C2C12 myoblasts generated using CRISPR/Cas9 method differentiate despite the expected derepression of the miRNA targets. Surprisingly, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 92 publications
(232 reference statements)
3
9
0
2
Order By: Relevance
“…However, a recent gene expression analysis of single SOL myofibers revealed that fast oxidative fibers (types IIa and IIx) are characterized by a stronger mitochondrial and electron transport chain signature than Type I, which is consistent with our overall change in gene expression and fiber type profiles (Chemello et al, 2019). In recently published work, a mouse in which miR-206 and both miR-1a loci were knocked out resulted in partial embryonic lethality, but miR-206 single KO mice and two surviving triple KO (tKO) individuals exhibited decreased physical performance, which was supported by impaired mitochondrial function in a tKO cell culture model (Przanowska et al, 2020). Although slow skeletal muscles were not examined in that study, it would be interesting to perform a metabolic analysis of slow oxidative muscles in single, double and triple miR-1/206 family KO mice.…”
Section: Discussionsupporting
confidence: 88%
“…However, a recent gene expression analysis of single SOL myofibers revealed that fast oxidative fibers (types IIa and IIx) are characterized by a stronger mitochondrial and electron transport chain signature than Type I, which is consistent with our overall change in gene expression and fiber type profiles (Chemello et al, 2019). In recently published work, a mouse in which miR-206 and both miR-1a loci were knocked out resulted in partial embryonic lethality, but miR-206 single KO mice and two surviving triple KO (tKO) individuals exhibited decreased physical performance, which was supported by impaired mitochondrial function in a tKO cell culture model (Przanowska et al, 2020). Although slow skeletal muscles were not examined in that study, it would be interesting to perform a metabolic analysis of slow oxidative muscles in single, double and triple miR-1/206 family KO mice.…”
Section: Discussionsupporting
confidence: 88%
“…S2, B and C). However, similar to mouse skeletal muscle, where loss of miR-1 causes disruption of mitochondrial structure and function ( 11 , 23 ), we found that miR-1–deficient L1 larvae displayed significant fragmentation of the otherwise extensive tubular mitochondrial network in the body-wall muscle ( Fig. 1A and fig.…”
Section: Resultssupporting
confidence: 64%
“…However, the authors confirmed that miR-206 promotes myogenic cell differentiation by suppressing factors preventing its progression, i.e., PAX7 as well as NOTCH3 and IGFBP5 [57]. This stays in line with the report by Przanowska et al, 2020, who revealed that triple knockout mice devoid of miR206/miR1a1/miR1a2 are characterized by a higher number of PAX7 positive cells [58]. Apart from MyomiRs, also other non-muscle-specific miRNAs are involved in the formation and functioning of skeletal muscles.…”
Section: Mirnasupporting
confidence: 81%